Growth and flowering of water stressed starfruit plants and responses to ameliorate water stress - Ismail, Mohd Razi; Yusoff, Mohd Kamil; Masturi, Afandi (1996)
Young starfruit (Averrhoa carambola L) plants grown in large soil volume were exposed to different moisture regime of 88-100% (moderate water stress) and 42-48% (severe water stress). Leaf and root growth were reduced with increased water stressed. A greater allocation of dry matter to the root, resulted to a higher root:shoot ratio in water stressed plants. In well watered plants, flower initiation was delayed. In an attempt to ameliorate water stress, leaf survival of stressed plants was enhanced by incorporating hydrogel polymer as compared to the application ABA on leaves.